2021
DOI: 10.1002/ange.202107785
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Unstable Picrotoxinin Hydrolysis Product

Abstract: The plant metabolite picrotoxinin (PXN) is a widely used tool in neuroscience for the identification of GABAergic signaling. Its hydrolysis in weakly alkaline media has been observed for over a century and the structure of the unstable hydrolysis intermediate was assigned by analogy to the degradation product picrotoxic acid. Here we show this assignment to be in error and we revise the structure of the hydrolysis product by spectroscopic characterization in situ. Counterintuitively, hydrolysis occurs at a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…13b We observed the initial (kinetic) site of hydrolysis with 1 equiv. NaOH to be C11, 26 and exposure to excess base led to complex decomposition. 27 We hypothesized that this latter decomposition derived from irreversible C15 hydrolysis -a "point of no return" due to concomitant epoxide opening or cyclohexane relaxation, with no precedent for chemical or biochemical reversion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13b We observed the initial (kinetic) site of hydrolysis with 1 equiv. NaOH to be C11, 26 and exposure to excess base led to complex decomposition. 27 We hypothesized that this latter decomposition derived from irreversible C15 hydrolysis -a "point of no return" due to concomitant epoxide opening or cyclohexane relaxation, with no precedent for chemical or biochemical reversion.…”
mentioning
confidence: 99%
“…Due to the translational potential of these observations, we also investigated the relative rates of hydrolysis observed in mouse plasma. C5 methylation led to a doubling of the extrapolated half-life in plasma (Figure 3e), likely a mixture of reversible C11 hydrolysis 26 and irreversible C15 hydrolysis. 13b No prior studies have identified PXN modifications that enhance metabolic stability.…”
mentioning
confidence: 99%